A weak spectral signature of water vapour in the atmosphere of HD 179949 b at high spectral resolution in the L band. Issue 1 (14th March 2020) - Webb, Rebecca K; Brogi, Matteo; Gandhi, Siddharth; Line, Michael R; Birkby, Jayne L; Chubb, Katy L; Snellen, Ignas A G; Yurchenko, Sergey N
ABSTRACT: High-resolution spectroscopy (R 20 000 ) is currently the only known method to constrain the orbital solution and atmospheric properties of non-transiting hot Jupiters. It does so by resolving the spectral features of the planet into a forest of spectral lines and directly observing its Doppler shift while orbiting the host star. In this study, we analyse VLT/CRIRES (R=100 000 ) L -band observations of the non-transiting giant planet HD 179949 b centred around 3.5 μ m . We observe a weak (3.0σ, or S/N = 4.8) spectral signature of H2 O in absorption contained within the radial velocity of the planet at superior-conjunction, with a mild dependence on the choice of line list used for the modelling. Combining this data with previous observations in the K band, we measure a detection significance of 8.4 σ for an atmosphere that is most consistent with a shallow lapse-rate, solar C/O ratio, and with CO and H2 O being the only major sources of opacity in this wavelength range. As the two sets of data were taken 3 yr apart, this points to the absence of strong radial-velocity anomalies due, e.g. to variability in atmospheric circulation. We measure a projected orbital velocity for the planet of K P = (145.2 ± 2.0) km s −1 (1σ) and improve the error bars on this parameter by ∼70 per cent. However, we only marginally tighten constraints on orbital inclination (66.2^+3.7_-3.1 deg) and planet mass (0.963^+0.036_-0.031 Jupiter masses), due to the dominant uncertainties of stellar mass and semimajor axis. Follow ups of radial-velocity planets are thus crucial to fully enable their accurate characterization via high-resolution spectroscopy.